Remote detection and monitoring of post-mining heat island - Worsa-Kozak, Magdalena; Górniak-Zimroz, Justyna; Szrek, Aleksandra; Chudy, Krzysztof (Frontiers in Environmental Science, 2024)
Underground hard coal mining activity in southern Poland has lasted more than 200 years. Among many factors related to mining and influencing the natural environment, the longest-active are coal waste heaps and tailings ponds. Several hundred objects are inventoried in Lower and Upper Silesia, of which 109 are located in the Lower Silesian Coal Basin (LSCB). These remnants of mining activity are built of gangue, waste coal, and coal silt (post-mining wastes). They cause environmental hazards, i.e., soil, air, groundwater, and surface water pollution in the storage area. They also tend to combust spontaneously, emitting enormous amounts of greenhouse gases into the atmosphere and increasing their neighborhood's air, soil, and water temperature. Indigenous fires occur more than 20 years after the end of the waste disposal phase. The post-mining heat island (PMHI) phenomena, related to thermal activity development of the post-coal mining heaps and tailings ponds, is still under-recognition and research. Therefore, our study aims to improve and develop a methodology for remote detection and monitoring of heat islands resulting from coal mining operations to track the thermal activity of heaps and tailings ponds in LSCB from mines closure to 2023. The study used open satellite data from the Landsat program to identify and track post-mining heat islands over 23 years within the former mining area and verify the results within the borders of the inventoried heaps and tailings ponds. As a result, geospatial analysis on a time scale was carried out to identify post-mining hot spots. The self-heating intensity index (SHII) and the air temperature thermal indicator (ATTI) were calculated for identified and confirmed objects. SHII ranged between 0.000 and 10.065, and ATTI, on the other hand, varied from -12.68 to 25.18. Moreover, maps of the thermal activity of selected heaps were developed, the characteristics of the self-combustion phenomena were identified, and the remote detection of PMHI and its monitoring methodology was developed. The provided method can be used in the future for regularly monitoring coal mining areas to prevent and identify hazardous hot spots and verify the maturity stage of the self-combustion processes.